Mutation profiles of oral squamous cell carcinoma cells - Xun Chen; Wei Zhao; Shangwu Chen; Dongsheng Yu (Elsevier, 2021)
Somatic mutation is associated with the occurrence, development and recurrence of oral cancer. Oral squamous cell carcinoma cell lines have been widely used in oral cancer research. So it's important to understand their genetic background, especially the mutation profile. Using the data of The Catalogue Of Somatic Mutations In Cancer (COSMIC), we analyzed the mutation characteristics of six tongue squamous cell carcinoma cell lines, identified the most common mutation cancer genes in oral squamous cell carcinoma, and compared these genes with those in colon cancer and lung cancer. Six tongue cancer cells have similar mutation spectrum in the coding region, of which C > T transition is the most common mutation, mainly located in the context of CpG dinucleotides. Profiles of mutation genes vary in different tongue cancer cell lines and TP53 is the most common mutation gene, followed by CDKN2A, KMT2D, and LRP1B. The 20 most common mutation genes in oral cancer are different from those in colon cancer and lung cancer, although TP53 is the most common mutation gene in these three cancers. The mutation characteristics of tongue cancer cell lines and mutation gene profiles of oral cancer provide valuable information for the study of oral cancers.